(untitled) (LACCEI, 2024)
The objective of the research is to provide information on the culture conditions that influence the growth of red macroalgae. A systematic review was developed selecting 19 articles, they were distributed according to the specific objectives: reproduction method, environmental parameters and culture systems. Among the reproduction methods, asexual propagation is mostly applied, being the tissue cultures with the highest growth rate (7.01 %/day DGR). The environmental parameters for controlled conditions are maintained between 19-31°C temperature, 40-60 μmol photons m-2s-1 of irradiance and natural light hours:darkness, and in the field a temperature of 27-34°C is commonly measured, 28.31 ppt salinity, 6-8 pH, and 5-8 mg/L dissolved oxygen. Among the culture systems, Long Line gave higher growth rates (5.84 - 7.01 %/day) than “palangre” (2.8-6.18 %/day) in the case of the most studied species, Kappaphycus alvarezii. In conclusion, the method of asexual reproduction, the environmental parameters in culture of temperature, irradiance and light hours:darkness, and field measurements of temperature, salinity, pH and dissolved oxygen and the use of the Long Line culture system, are the ones that give the highest growth rates for red macroalgae